CD19 expression in acute leukemia is not restricted to the cytogenetically aberrant populations. Issue 7 (1st July 2013) - Francis, Jawad; Dharmadhikari, Avinash V.; Sait, Sheila N. J.; Deeb, George; Wallace, Paul K.; Thompson, James E.; Wang, Eunice S.; Wetzler, Meir
Abstract: Aberrant expression of the B lymphoid marker, CD19, in acute myeloid leukemia (AML) has frequently been associated with t(8;21)(q22;q22). However, AML cases lacking t(8;21) may occasionally express CD19. We asked whether CD19 expression is restricted to the karyotypically abnormal leukemic cells in primary leukemia samples. We compared, by fluorescence in situ hybridization, CD19-positive and CD19-negative cells from nine patients with acute leukemia: three non-t(8;21) AML, three t(8;21) AML and three cases of acute lymphoblastic leukemia. There were no significant differences in karyotypic pattern between the CD19-positive and CD19-negative leukemic cells, raising the concern that therapeutically targeting CD19 for acute leukemia may not eradicate all malignant clones.